2011
DOI: 10.1167/iovs.11-7177
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Corneoscleral Topography on Soft Contact Lens Fit

Abstract: The extra peripheral corneoscleral data gained from OCT characterization of ocular surface architecture provide valuable insight into soft contact lens fit dynamics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
100
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(114 citation statements)
references
References 19 publications
11
100
3
Order By: Relevance
“…This factor, which now can be assessed with OCT instruments, has been shown to be of value in predicting contact lens fit. 22 Although nasal and temporal limbal shapes are known to differ, 22 our data showed no statistical difference between the effects of the contact lenses on the ocular surface on the nasal versus temporal sides of the eye.…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…This factor, which now can be assessed with OCT instruments, has been shown to be of value in predicting contact lens fit. 22 Although nasal and temporal limbal shapes are known to differ, 22 our data showed no statistical difference between the effects of the contact lenses on the ocular surface on the nasal versus temporal sides of the eye.…”
Section: Discussionmentioning
confidence: 47%
“…The topography of the limbus and sclera is not well defined; however, it is generally thought to have a flatter radius of curvature than the central and peripheral cornea in most meridians. 2,22 Depending on factors such as the design of the back surface of the contact lens and its biomechanical wrapping properties, the edge of a soft lens is likely to exert pressure on the ocular surface. So called ''limbal indentation'' is a well-known clinical manifestation of a tight-fitting soft contact lens 2 ; however, the soft lens fits in our study would not be classified as tight.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that changing the base curve of a soft lens does not generally have a significant effect on lens fit [16] and this is because the lens fit is influenced by peripheral corneal topography [19] and the corneoscleral anatomy [20]. Currently marketed daily disposable silicone-hydrogel contact lenses differ in shape profile and material composition and the lack of correlation in lens fit between the brands indicates these features affect the lens fit differently for individual patients.…”
Section: Discussionmentioning
confidence: 99%
“…Also, measuring techniques, up to recently limited to central keratometry, have been upgraded: first to limbal-to-limbal corneal coverage topography instruments, and most recently to instruments that can measure the limbal area and even beyond that (such as optical coherence tomography [3][4][5] and eye surface profilometry [6,7]), thus helping us better understand the shape of the corneo-scleral junction and the anterior surface. Studies by Hall et al [8] have indicated that there is a direct relationship between corneo-scleral shape and soft lens fitting characteristics. Additionally, we have ways to better measure, analyse and understand the shape and geometry of currently used soft contact lenses.…”
mentioning
confidence: 99%